2013
DOI: 10.1523/jneurosci.3633-12.2014
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Neurotransmission by GPCRs Is Dependent upon the Microarchitecture of the Primed Vesicle Complex

Abstract: G i/o -protein-coupled receptors (GPCRs) ubiquitously inhibit neurotransmission, principally via G␤␥, which acts via a number of possible effectors. GPCR effector specificity has traditionally been attributed to G␣, based on G␣'s preferential effector targeting in vitro compared with G␤␥'s promiscuous targeting of various effectors. In synapses, however, G␤␥ clearly targets unique effectors in a receptordependent way to modulate synaptic transmission. It remains unknown whether G␤␥ specificity in vivo is due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(98 citation statements)
references
References 73 publications
6
92
0
Order By: Relevance
“…Injection of an exogenous mutant SNAP25 containing these eight residues mutated to Ala with a botulinum toxin E (BoNT/E) resistance site into presynaptic neurons, along with BoNT/E light-chain protease, restores fusion while abrogating the ability of serotonin [5-hydroxytryptamine (5-HT)] to inhibit vesicle release in lamprey reticulospinal axons . Interestingly, data were recently shown supporting the notion that a distinct "microarchitecture" is prevalent at presynaptic 5-HT 1b receptors, predisposing them to this mode of Gbg-driven inhibition, whereas other microarchitectures both within the same synapses and within other types of synapses function through other mechanisms, such as the Gbg-mediated inhibition of calcium influx through voltage-gated calcium channels at the GABA B receptor (Hamid et al, 2014). From this, our current understanding of presynaptic inhibition is that presynaptic G i/o -coupled GPCRs function through a variety of mechanisms, including the direct binding of Gbg to SNAP25.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Injection of an exogenous mutant SNAP25 containing these eight residues mutated to Ala with a botulinum toxin E (BoNT/E) resistance site into presynaptic neurons, along with BoNT/E light-chain protease, restores fusion while abrogating the ability of serotonin [5-hydroxytryptamine (5-HT)] to inhibit vesicle release in lamprey reticulospinal axons . Interestingly, data were recently shown supporting the notion that a distinct "microarchitecture" is prevalent at presynaptic 5-HT 1b receptors, predisposing them to this mode of Gbg-driven inhibition, whereas other microarchitectures both within the same synapses and within other types of synapses function through other mechanisms, such as the Gbg-mediated inhibition of calcium influx through voltage-gated calcium channels at the GABA B receptor (Hamid et al, 2014). From this, our current understanding of presynaptic inhibition is that presynaptic G i/o -coupled GPCRs function through a variety of mechanisms, including the direct binding of Gbg to SNAP25.…”
Section: Introductionmentioning
confidence: 88%
“…One well-studied mechanism is the direct binding of G protein bg subunits to voltage-gated calcium channels, leading to voltage-dependent inhibition of calcium entry (Ikeda, 1996). The ability of G i/o -coupled GPCRs to inhibit exocytosis downstream of voltage-gated calcium channels is well documented in a number of different cell types (Blackmer et al, 2001;Delaney et al, 2007;Yoon et al, 2008;Iremonger and Bains, 2009;Zhao et al, 2010;Hamid et al, 2014). We have previously demonstrated that inhibition can also occur through the direct interaction of Gbg with the soluble N-ethylmaleimide attachment protein receptor (SNARE) protein SNAP25 Gerachshenko et al, 2005;Yoon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although the tiger salamander SNAP-25 sequence is unknown, this site and the rest of the SNAP-25 C terminus are largely conserved in the Japanese fire belly newt (Cynops pyrrhogaster, GenBank accession #BAE47569.1), another amphibian related to the tiger salamander. The actions of BoNT/A at this site have been shown to inhibit G␤␥-SNAP-25 interactions and G␤␥-mediated reductions in synaptic transmission in other neurons (Gerachshenko et al, Delaney et al, 2007;Hamid et al, 2014). In recordings from tissue treated with BoNT/A (n ϭ 5 cone-HC pairs), L-AP4 application resulted in a nonsignificant 8 Ϯ 4% increase in I Ca (p ϭ 0.14, paired t test; n ϭ 5) and a nonsignificant 7 Ϯ 4% reduction in the EPSC amplitude (p ϭ 0.17, paired t test; n ϭ 5).…”
Section: Resultsmentioning
confidence: 99%
“…) over, direct introduction of G␤␥ subunits dose-dependently inhibited exocytosis, and this effect was inhibited by BoNT/A pretreatment. G␤␥-SNARE interactions triggered by G i/o -coupled GPCRs have been identified in a handful of other synapses: in mammals, the hippocampal CA1-subicular synapse (Hamid et al, 2014), Schaeffer collateral-CA1 synapses (Zhang et al, 2011), and inputs to the amygdala (Delaney et al, 2007), and in lamprey, reticulospinal axon synapses .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation